Effect of N-Acetylcysteine on Dyslipidemia and Carbohydrate Metabolism in STZ-Induced Diabetic Rats - Anderson Kiyoshi Kaga; Pedro Octavio Barbanera; Nágilla Orleanne Lima do Carmo; Lucas Rodolfo de Oliveira Rosa; Ana Angélica Henrique Fernandes (International Journal of Vascular Medicine)
Background. Type 1 diabetes mellitus (T1DM) is characterized by insulin-deficient production leading to hyperglycemia, which is associated with diabetic complications such as cardiovascular diseases. Antioxidants have been proving a good alternative to diabetic complications, with N-acetylcysteine (NAC) having antioxidant characteristics. The aim of this study was to assess the effect of NAC on the lipid profile and the atherogenic index (AI) in streptozotocin- (STZ-) induced diabetic rats. Method. 32 male Wistar rats (60 days of age) weighting ±250 g were randomly distributed into four groups (n=8): CTRL: control rats; CTRL+NAC: control rats treated with NAC; DM: diabetic rats; DM+NAC: diabetic rats treated with NAC. T1DM was induced using STZ (60 mg/kg, ip; single dose), and NAC (25 mg/kg/day) was administrated by gavage, for 37 days. The animals received chow and water ad libitum. After the experimental period, blood and cardiac tissue samples were collected to analyze energetic metabolism, lipid profile, and AI. Results. NAC decreased (p<0.01) glycemia, energy intake, carbohydrate, and protein consumption in diabetic rats (DM+NAC), when compared with DM, while the alimentary efficiency was improved (p<0.01) in treated diabetic rats (DM+NAC). Diabetic rats treated with NAC decreased (p<0.01) lipid profile and AI in diabetic rats (DM+NAC) when compared to DM. Conclusion. NAC improves lipid profile and decreases AI in STZ-induced diabetic rats.